2022
DOI: 10.3390/biom12091248
|View full text |Cite
|
Sign up to set email alerts
|

Iron in Alzheimer’s Disease: From Physiology to Disease Disabilities

Abstract: Reactive Oxygen Species (ROS) play a key role in the neurodegeneration processes. Increased oxidative stress damages lipids, proteins, and nucleic acids in brain tissue, and it is tied to the loss of biometal homeostasis. For this reason, attention has been focused on transition metals involved in several biochemical reactions producing ROS. Even though a bulk of evidence has uncovered the role of metals in the generation of the toxic pathways at the base of Alzheimer’s disease (AD), this matter has been sidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 186 publications
0
18
0
1
Order By: Relevance
“…[ 17 ] Hepcidin and IL‐6 play a key role in host defense mechanisms linked to neuroinflammation. [ 60 ] Research has shown that inflammation leads to increased expression of DMT1 in neurons and increased expression of hepcidin in astrocytes and microglia. In contrast, the expression of FPN is decreased by hepcidin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Hepcidin and IL‐6 play a key role in host defense mechanisms linked to neuroinflammation. [ 60 ] Research has shown that inflammation leads to increased expression of DMT1 in neurons and increased expression of hepcidin in astrocytes and microglia. In contrast, the expression of FPN is decreased by hepcidin.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of iron homeostasis has been linked to the pathogenesis and progression of neurodegenerative mechanisms such as AD and Parkinson's disease. [58][59][60] It has been reported that iron is enriched in amyloid plaques and neurofibrillary tangles in the brains of AD patients. [23,61] Cortical iron may contribute to the deterioration of cognitive pathology and may potentially induce oxidative stress or be associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Fe helps the immune system, cognitive, and connective tissue functionality. We absorb only as much Fe as we need, on average 1–2 mg/day (reviewed in [ 33 ]). Fe absorption is, in fact, highly regulated, and the metal is not excreted, but recycled; our body loses some Fe only by indirect processes (e.g., sloughing of skin, minor hemorrhages, and menstruation in women), but in very little amounts (about 1–2 mg/day).…”
Section: Essential Metals In Physiologymentioning
confidence: 99%
“…Fe levels in the blood are regulated by hepcidin, a hormone that is biosynthesized in the liver. Hepcidin regulates the degradation rate of ferroportin in the enterocyte membrane, and, as a result, the rate of Fe export from the enterocyte to the blood (reviewed in [ 33 ]).…”
Section: Essential Metals In Physiologymentioning
confidence: 99%
See 1 more Smart Citation